Chronic intermittent psychological stress promotes macrophage reverse cholesterol transport by impairing bile acid absorption in mice. Issue 5 (11th May 2015) - Silvennoinen, Reija; Quesada, Helena; Kareinen, Ilona; Julve, Josep; Kaipiainen, Leena; Gylling, Helena; Blanco‐Vaca, Francisco; Escola‐Gil, Joan Carles; Kovanen, Petri T.; Lee‐Rueckert, Miriam
Abstract: Psychological stress is a risk factor for atherosclerosis, yet the pathophysiological mechanisms involved remain elusive. The transfer of cholesterol from macrophage foam cells to liver and feces (the macrophage‐specific reverse cholesterol transport, m‐RCT) is an important antiatherogenic pathway. Because exposure of mice to physical restraint, a model of psychological stress, increases serum levels of corticosterone, and as bile acid homeostasis is disrupted in glucocorticoid‐treated animals, we investigated if chronic intermittent restraint stress would modify m‐RCT by altering the enterohepatic circulation of bile acids. C57Bl/6J mice exposed to intermittent stress for 5 days exhibited increased transit through the large intestine and enhanced fecal bile acid excretion. Of the transcription factors and transporters that regulate bile acid homeostasis, the mRNA expression levels of the hepatic farnesoid X receptor (FXR), the bile salt export pump (BSEP), and the intestinal fibroblast growth factor 15 (FGF15) were reduced, whereas those of the ileal apical sodium‐dependent bile acid transporter (ASBT), responsible for active bile acid absorption, remained unchanged. Neither did the hepatic expression of cholesterol 7 α ‐hydroxylase (CYP7A1), the key enzyme regulating bile acid synthesis, change in the stressed mice. Evaluation of the functionality of the m‐RCT pathway revealed increased fecal excretion of bile acids that had been synthesized from macrophage‐derived cholesterol. Overall, our study reveals that chronic intermittent stress in mice accelerates m‐RCT specifically by increasing fecal excretion of bile acids. This novel mechanism of m‐RCT induction could have antiatherogenic potential under conditions of chronic stress. Abstract : Macrophage‐specific reverse cholesterol transport (m‐RCT) is an important antiatherogenic pathway which directs cholesterol and bile acids made thereof for fecal excretion. In this study, we found that chronic intermittent restraint stress, a model of psychological stress, stimulated large intestinal transit which specifically hampered bile acid absorption, and so accelerated the m‐RCT pathway in mice. This novel mechanism of m‐RCT induction could have antiatherogenic potential under conditions of chronic stress.